The Bravery in the Nun Movie Directed By Cordin Hardy - Maulani Pangestu; Istihayyu Buansari; Dwi Indah Lestari (Wanastra: Jurnal Bahasa dan Sastra, 2021)
The purpose of research is to find out what courage is and how many types of courage. This research was conducted by using a film as a source entitled The Nun which was released in 2018, directed by Corin Hardly. The author wants to analyze the causes of courage. The author chooses the film The Nun and the main character as the object of this study. The method of this research is descriptive qualitative. The results of this study are: (1) Causes of courage from the main character based on Rahman's theory: Confidence, Situational Demands, Altruism and Emotional and Cognitive Resources (2) Actions of courage from the main character: St.Carta Monastery of Romania, he left the Substitute for searching for truth, proving the Truth (3) The moral values of the film: truths that teach how to deal with our lives because humans must always struggle and do not give up in any situations. Courage is one of the most important qualities we must have. Having courage can help us achieve extraordinary things in social life. We also need courage to give good and positive things to those around us.